Fifty key thinkers in criminology - Hayward, Keith J.; Maruna, Shadd; Mooney, Jayne (Routledge key guides., 2010)
Presenting the history of criminological thought, this book covers a range of historical and contemporary thinkers from around the world, offering a combination of biographical fact with historical and cultural context.